Moreton Bay; A previously unrecognized resting stopover for east-coast of Australia migrating humpback whales - Castrillon, Juliana; Mayaud, Raphael; Wilson, Craig; Dalle Luche, Greta; Allen, Jenny; Bengtson Nash, Susan (Frontiers in Marine Science, 2023)
Humpback whales enter Moreton Bay, in southeast Queensland, Australia, each year during their annual migration. Little is known about the ecological significance of the bay for the humpback whale population. In a region characterised by rapid coastal and maritime development, as well as a growing humpback whale population, there is an urgent need to fill knowledge gaps surrounding the populations’ seasonal distribution and habitat use in these coastal waters. This study procured the first detailed information regarding humpback whale distribution, behaviour, and habitat use within Moreton Bay, relative to the main east coast migratory corridor. It was found that on average 42.41% of the individuals observed on the southern leg of the migration entered the bay. 76.78% of pods entering the bay had accompanying calves and 47.82% of these pods were found to be resting or logging, a behaviour often associated with nursing, at the time of observation. These findings provide strong evidence for a previously undocumented role of Moreton Bay as a resting stopover for migrating humpback whales.